Determinants of the degree of penalty against independent auditors in Brazil - Juliana Bacelar de Freitas; Jakeline Patrícia Santos; José Alves Dantas (Revista Contemporânea de Contabilidade, 2020)
The importance of auditing in the capital market, for its trust and credibility, has increased with business development. Thus, this research aimed to identify the determinants of the degree of penalties applied against independent auditors, based on the Sanctioning Administrative Proceedings filed by the Securities Commission (CVM) from 2000 to 2017. The study contributes to science being the first to look for variables that quantitatively explain these sanctions. The sample of 76 cases was taken from the CVM and B3 sites. The proposed regression models show that the penalties against auditors are: (i) positively and significantly related to breaches of client acceptance, execution and reporting of work, repeat offenders and listed client companies; (ii) negatively and significantly related to the occurrence of audit planning violations, the existence of corporate governance in the audited clients, big four firms and procedural times.